2018
DOI: 10.7150/jbji.28765
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Modified Debridement-Irrigation, Antibiotic Therapy and Implant Retention Protocol for the Management of Surgical Site Infections: A Series of 1694 Instrumented Spinal Surgery

Abstract: Introduction: Management of surgical site infections (SSI) after instrumented spinal surgery remains controversial. The debridement-irrigation, antibiotic therapy and implant retention protocol (DAIR protocol) is safe and effective to treat deep SSI occurring within the 3 months after instrumented spinal surgery.Methods: This retrospective study describes the outcomes of patients treated over a period of 42 months for deep SSI after instrumented spinal surgery according to a modified DAIR protocol.Results: Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…Of these, only 49 articles were found relevant, and were used for the synthesis below. 8 56 Below is the summary of their findings. Relevancy was determined purely based on if the articles answered any one of the following: (1) implant removal rate, (2) common bacterial organisms found following infection, (3) time of onset, and (4) ratio of superficial to deep infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, only 49 articles were found relevant, and were used for the synthesis below. 8 56 Below is the summary of their findings. Relevancy was determined purely based on if the articles answered any one of the following: (1) implant removal rate, (2) common bacterial organisms found following infection, (3) time of onset, and (4) ratio of superficial to deep infection.…”
Section: Resultsmentioning
confidence: 99%
“…39 Key steps for management included irrigation and debridement, vacuum-assisted wound closure (VAC) in 25% and more cases, and variable term antibiotics administration (both intravenous and oral). [17][18][19][20]24,28,31,36,39,44,[46][47][48][49][50][51][52][53] Many authors concluded that eradication of deep SSIs was not possible without complete removal of spinal implants. In addition, repeated site debridement could not eradicate SSI either while the implants (pedicular and/or interbody constructs) were retained, and therefore removal in most or all patients was later necessary.…”
Section: Discussionmentioning
confidence: 99%
“…49 All authors agree that cephalosporin prophylaxis should be started at a maximum of 1 hour prior to incision. 10,29,39,49,50,61,65 A repeated prophylaxis was performed by Collins et al when surgery was more than 2 hours, 31 by Liu, Lamberet and Litrico et al in operations longer than 4 hours, 10,49,72 by Fang et al after 6 hours of surgery or significant blood loss, 13 and by Pull ter Gunne et al after 4 hours or 1.5-liter blood loss. 29,61 In contrast, some authors suggest a prolonged antibiotic prophylaxis not only in selected cases but rather as a postoperative standard in all cases, independently of surgery time or 70 and Chang et al for up to 5 days.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“… 47 - 49 Thereby, a second look surgery might improve the therapeutic outcome in DAIR. 50 In this context, the role of DAIR in chronic cases unable to undergo implant removal / exchange due to instability or perioperative factors remains unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation